(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1872)
This article covers the author’s visit to the vitrified fort at Dun Mac Sniachan in 1869. He briefly discusses the fort’s history and describes the remaining visible features. He goes on to discuss what some of the local historical sites and finds can tell us about historical human habitation in the area. The author also analyses the process of the fort’s vitrification, the formation of peat and the composition of peat ash. Finally he describes the remains of what he believes to be a crannog and some nearby cairns and burial sites, speculating when they may have been built.